Ferulic acid-containing particle, ultraviolet absorber, and cosmetic raw material

Ferulic acid-containing particles with uniform dispersion in inorganic particles and optional additives improve ultraviolet absorbability, achieving high SPF and UVAPF values.

JP2025010087APending Publication Date: 2025-01-20OSAKA GAS CHEM KK
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024107138
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-05
Filing Date
2024-07-03
Publication Date
2025-01-20

AI Technical Summary

Technical Problem

Simply mixing ferulic acid with inorganic particles in cosmetics does not provide adequate ultraviolet absorbability.

Method used

Ferulic acid-containing particles are formulated with a minimum 5% by mass ferulic acid uniformly dispersed in inorganic particles, along with optional salts of carboxyl group-containing compounds or polyvinylpyrrolidone to enhance dispersion and absorption.

Benefits of technology

The formulation achieves an SPF value of 20 or more and UVAPF value of 6 or more, ensuring excellent ultraviolet absorption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025010087000002
    Figure 2025010087000002
  • Figure 2025010087000003
    Figure 2025010087000003
  • Figure 2025010087000004
    Figure 2025010087000004
Patent Text Reader

Abstract

To provide ferulic acid-containing particles with superior UV absorbency, an ultraviolet absorber containing the ferulic acid-containing particles, and a cosmetic raw material containing the ferulic acid-containing particles.SOLUTION: Ferulic acid-containing particles comprise inorganic particles and ferulic acid. The content of the ferulic acid is 5 mass% or more relative to the ferulic acid-containing particles. The ferulic acid exhibits uniform dispersion in the inorganic particles.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to ferulic acid-containing particles, an ultraviolet absorber, and a cosmetic raw material. [Background technology]

[0002] Conventionally, cosmetics contain ingredients that have ultraviolet absorbing properties.

[0003] As an example of a component having ultraviolet absorbing properties, ferulic acid has been proposed (see, for example, Non-Patent Document 1). [Prior art documents] [Patent documents]

[0004] [Non-Patent Document 1] Ferulic Acid Catalog ver.2.2ST, Oryza Oil & Fat Chemical Co., Ltd., January 20, 2015 Summary of the Invention [Problem to be solved by the invention]

[0005] As a method for incorporating ferulic acid into cosmetics, a method is being considered in which ferulic acid is mixed with inorganic particles to form ferulic acid-containing particles, which are then incorporated into the cosmetics.

[0006] However, there is a problem in that simply mixing ferulic acid with inorganic particles does not result in good ultraviolet absorbing properties.

[0007] The present invention provides ferulic acid-containing particles having excellent ultraviolet absorbing properties, an ultraviolet absorber containing the ferulic acid-containing particles, and a cosmetic raw material containing the ferulic acid-containing particles. [Means for solving the problem]

[0008] The present invention [1] is a ferulic acid-containing particle comprising inorganic particles and ferulic acid, wherein the content of ferulic acid is 5 mass% or more relative to the ferulic acid-containing particle, and the ferulic acid is uniformly dispersed within the inorganic particles.

[0009] The present invention [2] contains ferulic acid-containing particles as described in claim 1, having an SPF value of 20 or more.

[0010] The present invention [3] includes an ultraviolet absorber comprising the ferulic acid-containing particles described in [1] or [2] above.

[0011] The present invention [4] includes a cosmetic raw material comprising the ferulic acid-containing particles described in [1] or [2] above. Effect of the Invention

[0012] In the ferulic acid-containing particles of the present invention, the content of ferulic acid is equal to or greater than a predetermined value, and the ferulic acid is uniformly dispersed in the inorganic particles, so that the particles have excellent ultraviolet absorbing properties.

[0013] The ultraviolet absorbent of the present invention contains the ferulic acid-containing particles of the present invention, and therefore has excellent ultraviolet absorbing properties.

[0014] The cosmetic raw material of the present invention contains the ferulic acid-containing particles of the present invention, and therefore has excellent ultraviolet absorbing properties. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 shows an SEM photograph of the ferulic acid-containing particles of Example 1. [Diagram 2] FIG. 2 shows an SEM photograph of the ferulic acid-containing particles of Example 2. [Diagram 3] FIG. 3 shows an SEM photograph of the ferulic acid-containing particles of Example 3. [Figure 4] FIG. 4 shows an SEM photograph of the ferulic acid-containing particles of Example 4. [Diagram 5]FIG. 5 shows an SEM photograph of the ferulic acid-containing particles of Example 5. [Figure 6] FIG. 6 shows an SEM photograph of the ferulic acid-containing particles of Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] <Ferrulic acid-containing particles> The ferulic acid-containing particles include inorganic particles and ferulic acid. More specifically, the ferulic acid-containing particles include inorganic particles and ferulic acid uniformly dispersed in the inorganic particles.

[0017] [Inorganic particles] Examples of inorganic particles include those generally used in cosmetics.Specific examples of inorganic particles include talc, mica (natural and synthetic), sericite, kaolin, silica, calcium carbonate, aluminum oxide, zinc oxide, and titanium oxide.Preferably, inorganic particles include silica particles from the viewpoint of oil absorption.

[0018] The average particle size of the inorganic particles is, for example, 0.02 μm or more, preferably 0.1 μm or more, more preferably 1.0 μm or more, even more preferably 2.0 μm or more, and for example, 50 μm or less, preferably 10 μm or less, more preferably 6 μm or less.

[0019] The average particle size can be determined by creating a particle size distribution curve using a laser diffraction / scattering type particle size distribution analyzer and calculating the 50% by mass equivalent particle size.

[0020] The content ratio of the inorganic particles relative to the ferulic acid-containing particles is, for example, 60 mass% or more, preferably 70 mass% or more, more preferably 80 mass% or more, and for example, 90 mass% or less, preferably 85 mass% or less.

[0021] The inorganic particles can be used alone or in combination of two or more kinds.

[0022] [Ferulic acid] Ferulic acid is a component that has ultraviolet absorbing properties.

[0023] Ferulic acid includes structural isomers of trans-ferulic acid and cis-ferulic acid, and preferably trans-ferulic acid.

[0024] The content of ferulic acid in the ferulic acid-containing particles is 5% by mass or more, preferably 8% by mass or more, more preferably 10% by mass or more, even more preferably 12% by mass or more, particularly preferably 14% by mass or more, and for example, 30% by mass or less, preferably 25% by mass or less, more preferably 20% by mass or less, even more preferably 17% by mass or less.

[0025] When the content of ferulic acid is equal to or higher than the above lower limit, ultraviolet absorbing properties can be improved.

[0026] On the other hand, if the content of ferulic acid is less than the above lower limit, the ultraviolet ray absorbency decreases.

[0027] The content of ferulic acid can be measured by high performance liquid chromatography (HPLC), which will be described in detail in the Examples below.

[0028] Moreover, ferulic acid is uniformly dispersed in inorganic particles. Therefore, it has excellent ultraviolet absorbing properties. Moreover, "uniformly dispersed" means that, as can be seen from the SEM photograph shown in the examples described later, ferulic acid is supported (fixed or embedded, preferably supported in the pores of inorganic particles) on the surface of inorganic particles, and ferulic acid is not crystallized independently of inorganic particles. That is, ferulic acid-containing particles do not contain crystals of ferulic acid independent of inorganic particles. Crystals of ferulic acid independent of inorganic particles specifically mean at least crystals of ferulic acid independent of inorganic particles having a major axis exceeding 11.0 μm or a minor axis exceeding 5.0 μm.

[0029] The ferulic acid-containing particles may also contain ferulic acid crystals deposited on the surface of inorganic particles. The major axis of the ferulic acid crystals deposited on the surface of inorganic particles is, for example, 11.0 μm or less, preferably 10.0 μm or less, more preferably 8.0 μm or less, and even more preferably 7.0 μm or less. The minor axis of the ferulic acid crystals deposited on the surface of inorganic particles is, for example, 5.0 μm or less, preferably 4.0 μm or less, and more preferably 2.0 μm or less. From the viewpoint of improving the touch (specifically, the touch required for cosmetic raw materials), the ferulic acid-containing particles preferably do not contain ferulic acid crystals deposited on the surface of inorganic particles.

[0030] The major axis and the minor axis can be measured by SEM.

[0031] Preferably, from the viewpoint of improving the tactile sensation (specifically, the skin tactile sensation required for cosmetic raw materials), ferulic acid is supported within the pores of inorganic particles.

[0032] [Salts of carboxyl-containing compounds and polyvinylpyrrolidone] The ferulic acid-containing particles preferably contain a salt of a carboxyl group-containing compound or polyvinylpyrrolidone.

[0033] When the ferulic acid-containing particles contain a salt of a carboxyl group-containing compound or polyvinylpyrrolidone, the ferulic acid can be prevented from precipitating in a ferulic acid solution used for producing the ferulic acid-containing particles, as described in detail below. This allows the ferulic acid to be more uniformly dispersed in the inorganic particles. As a result, the ultraviolet ray absorption can be improved.

[0034] (Salt of a carboxyl group-containing compound) The salt of the carboxyl group-containing compound is a component that suppresses the precipitation of ferulic acid in a ferulic acid solution described below. The salt of the carboxyl group-containing compound is dispersed in the inorganic particles together with ferulic acid.

[0035] In the salt of the carboxyl group-containing compound, examples of the carboxyl group-containing compound include a compound containing a hydroxyl group and a carboxyl group, and a carboxyl group-containing compound without a hydroxyl group.

[0036] The hydroxyl group- and carboxyl group-containing compound is a compound that contains a hydroxyl group in addition to a carboxyl group. Examples of the hydroxyl group- and carboxyl group-containing compound include glycolic acid, lactic acid, malic acid, tartaric acid, citric acid, 2-hydroxybutyric acid, 3-hydroxybutyric acid, 4-hydroxybutyric acid, tartronic acid, glyceric acid, ascorbic acid, gluconic acid, salicylic acid, 4-hydroxymethylbenzoic acid, mandelic acid, and benzilic acid, and preferably include lactic acid, citric acid, and ascorbic acid.

[0037] The non-hydroxyl group-containing carboxyl group compound is a compound that contains a carboxyl group but does not contain a hydroxyl group. Examples of the non-hydroxyl group-containing carboxyl group compound include acetic acid, butyric acid, and oxalic acid.

[0038] As the carboxyl group-containing compound, from the viewpoint of further suppressing the precipitation of ferulic acid, a hydroxyl group- and carboxyl group-containing compound is preferably used.

[0039] In addition, with regard to the salt of the carboxyl group-containing compound, examples of the salt include sodium salts and calcium salts, and preferably sodium salts.

[0040] As the salt of the carboxyl group-containing compound, preferably, there is mentioned a sodium salt of the hydroxyl group- and carboxyl group-containing compound. As the salt of the carboxyl group-containing compound, more preferably, there is mentioned a sodium salt of lactic acid, a sodium salt of citric acid, and a sodium salt of ascorbic acid. As the salt of the carboxyl group-containing compound, there is particularly preferably, there is mentioned a sodium salt of lactic acid, from the viewpoint of improving ultraviolet absorbing property.

[0041] The salts of the carboxyl group-containing compounds can be used alone or in combination of two or more kinds.

[0042] The content of the salt of the carboxyl group-containing compound is, for example, 5 mass % or more and, for example, 30 mass % or less, preferably 20 mass % or less, relative to the ferulic acid-containing particles.

[0043] (Polyvinylpyrrolidone) Polyvinylpyrrolidone is a component that suppresses the precipitation of ferulic acid in a ferulic acid solution described below. Polyvinylpyrrolidone is dispersed in the inorganic particles together with ferulic acid.

[0044] The number average molecular weight of polyvinylpyrrolidone is, for example, 1,000 or more, preferably 5,000 or more, more preferably 8,000 or more, and for example, 20,000 or less, preferably 15,000 or less, more preferably 12,000 or less.

[0045] When the number average molecular weight of polyvinylpyrrolidone is equal to or more than the above lower limit and equal to or less than the above upper limit, the precipitation of ferulic acid can be further suppressed.

[0046] The number average molecular weight of polyvinylpyrrolidone can be measured by gel permeation chromatography.

[0047] Moreover, commercially available polyvinylpyrrolidone can also be used, for example, PVP10 (manufactured by Strem Chemicals Inc.).

[0048] The content ratio of polyvinylpyrrolidone relative to the ferulic acid-containing particles is, for example, 5 mass % or more and, for example, 30 mass % or less, preferably 20 mass % or less.

[0049] From the viewpoint of further suppressing precipitation of ferulic acid in a ferulic acid solution, the ferulic acid-containing particles preferably do not contain polyvinylpyrrolidone but contain a salt of a carboxyl group-containing compound.

[0050] [Method of manufacturing ferulic acid-containing particles] The method for producing ferulic acid-containing particles includes a first step of preparing a ferulic acid solution, a second step of mixing the ferulic acid solution with inorganic particles, and a third step of obtaining ferulic acid-containing particles by drying an alcohol having 2 to 3 carbon atoms (described below) and water.

[0051] (1st step) In the first step, a ferulic acid solution is prepared.

[0052] The ferulic acid solution contains ferulic acid, an alcohol having 2 to 3 carbon atoms, water, and, if necessary, a salt of a carboxyl group-containing compound or polyvinylpyrrolidone. That is, the ferulic acid solution contains ferulic acid, an alcohol having 2 to 3 carbon atoms, water, and, if necessary, a salt of a carboxyl group-containing compound, or contains ferulic acid, an alcohol having 2 to 3 carbon atoms, water, and, if necessary, polyvinylpyrrolidone. Preferably, the ferulic acid solution is composed of ferulic acid, an alcohol having 2 to 3 carbon atoms, water, and a salt of a carboxyl group-containing compound, or ferulic acid, an alcohol having 2 to 3 carbon atoms, water, and polyvinylpyrrolidone.

[0053] {Ferulic acid} The content of ferulic acid (solid concentration of ferulic acid) in the ferulic acid solution is, from the viewpoint of improving ultraviolet absorbency, for example, 22.0 mass% or more, preferably 23.0 mass% or more, more preferably 24.0 mass% or more, even more preferably 25.0 mass% or more, particularly preferably 26.0 mass% or more, and for example, 31.8 mass% or less, preferably 30.0 mass% or less.

[0054] When the content of ferulic acid (solid content concentration of ferulic acid) is equal to or higher than the lower limit, the content of ferulic acid in the ferulic acid-containing particles can be equal to or higher than the predetermined value.

[0055] {Alcohol with 2 to 3 carbon atoms} Examples of alcohols having 2 to 3 carbon atoms (hereinafter, sometimes referred to as alcohols) include ethanol, 1-propanol, and 2-propanol. As the alcohol, ethanol is preferable. More preferably, the alcohol consists of ethanol.

[0056] The content of the alcohol relative to the ferulic acid solution is, for example, 30% by mass or more, preferably 40% by mass or more, more preferably 50% by mass or more, and for example, 70% by mass or less.

[0057] Alcohols can be used alone or in combination of two or more types.

[0058] {water} Water is a solvent in which ferulic acid dissolves.

[0059] The water content is, for example, 4 mass % or more, 6 mass % or more, and for example, 40 mass % or less, preferably 30 mass % or less, and more preferably 10 mass % or less, relative to the ferulic acid solution.

[0060] The mass ratio of alcohol to water (alcohol / water) is, for example, 1 or more, preferably 2 or more, more preferably 5 or more, and for example, 20 or less, preferably 15 or less, more preferably 10 or less.

[0061] When the mass ratio is equal to or greater than the lower limit, ferulic acid can be reliably dissolved in the ferulic acid solution.

[0062] {Salt of a carboxyl group-containing compound} The content of the salt of the carboxyl group-containing compound is, for example, more than 3 mass % and, for example, 20 mass % or less based on the ferulic acid solution.

[0063] The salt of the carboxyl group-containing compound can also be diluted with water to prepare an aqueous solution of the salt of the carboxyl group-containing compound. In the aqueous solution of the salt of the carboxyl group-containing compound, the solid content concentration of the salt of the carboxyl group-containing compound is, for example, 30% by mass or more, preferably 50% by mass or more, and 80% by mass or less.

[0064] {Polyvinylpyrrolidone} The content of polyvinylpyrrolidone is, for example, more than 3% by mass and, for example, 20% by mass or less, based on the ferulic acid solution.

[0065] {Preparation of ferulic acid solution} To prepare the ferulic acid solution, ferulic acid, alcohol, water, and, if necessary, a salt of a carboxyl group-containing compound or polyvinylpyrrolidone are mixed and heated so as to obtain the above-mentioned content ratio. In this case, the water in the aqueous solution of the salt of the carboxyl group-containing compound can be used as it is.

[0066] The heating temperature is 60° C. or higher, preferably 65° C. or higher.

[0067] If the heating temperature is equal to or higher than the lower limit, ferulic acid can be dissolved reliably.

[0068] The upper limit of the heating temperature is a temperature below the boiling point of the alcohol. For example, when the alcohol is ethanol, the upper limit of the heating temperature is 78° C. or lower, preferably 70° C. or lower.

[0069] In addition, the heating time is, from the viewpoint of reliably dissolving ferulic acid, for example, 1 minute or more, preferably 5 minutes or more, and for example, 120 minutes or less, preferably 60 minutes or less, more preferably 30 minutes or less, and even more preferably 20 minutes or less.

[0070] In this way, a ferulic acid solution is prepared. In addition, if the ferulic acid solution contains a salt of a carboxyl group-containing compound or polyvinylpyrrolidone, the precipitation of ferulic acid in the ferulic acid solution can be suppressed. This allows the ferulic acid to be more uniformly dispersed in the inorganic particles. As a result, the ultraviolet ray absorption can be improved.

[0071] (2nd process) In the second step, the ferulic acid solution and the inorganic particles are mixed.

[0072] Specifically, the ferulic acid solution is added dropwise to the inorganic particles all at once or in portions. Preferably, the ferulic acid solution is added dropwise to the inorganic particles in portions.

[0073] To drop the ferulic acid solution onto the inorganic particles in portions, a portion of the ferulic acid solution (for example, 5 parts by mass or more and 10 parts by mass or less per 100 parts by mass of the inorganic particles) is dropped onto the inorganic particles and stirred.

[0074] The stirring time is, for example, from 10 seconds to 60 seconds.

[0075] This operation is then repeated multiple times (for example, two or more times, and for example, ten or less times, preferably seven or less times). This allows ferulic acid to be more uniformly dispersed in the inorganic particles. As a result, ultraviolet light absorbency can be improved.

[0076] (3rd step) In the third step, the alcohol and water are dried to obtain ferulic acid-containing particles.

[0077] Specifically, the alcohol and water are dried using a vacuum dryer at, for example, 40° C. or higher, preferably 50° C. or higher, and for example, 60° C. or lower, for example, 12 hours or more, preferably 18 hours or more, and for example, 48 hours or less, preferably 36 hours or less.

[0078] This results in ferulic acid-containing particles containing the dried ferulic acid solution (specifically, ferulic acid and, if necessary, a salt of a carboxyl group-containing compound or polyvinylpyrrolidone) and inorganic particles. More specifically, in the ferulic acid-containing particles, the dried material is dispersed (supported) on the inorganic particles.

[0079] In such ferulic acid-containing particles, the content of ferulic acid is equal to or greater than a predetermined value, and the dried material (ferulic acid) is uniformly dispersed in the inorganic particles, resulting in excellent ultraviolet absorbing properties.

[0080] Specifically, the SPF value measured in the ultraviolet absorbance measurement described below is, for example, 15 or more, preferably 20 or more, more preferably 22 or more, even more preferably 25 or more, particularly preferably 28 or more, most preferably 30 or more, and is usually 100 or less. The SPF value is an acronym for "Sun Protection Factor" and is an index that indicates the degree of effect of blocking UVB waves among ultraviolet rays.

[0081] The UVAPF value measured in the ultraviolet absorbance measurement described later is, for example, 6 or more, preferably 7 or more, more preferably 8 or more, even more preferably 9 or more, particularly preferably 10 or more, and is usually 30 or less. The UVAPF value is an acronym for "Ultraviolet A Protection Factor" and is an index showing the degree of effect of blocking UVA waves among ultraviolet rays.

[0082] <Ultraviolet absorbing agent> The ultraviolet absorbing agent contains the ferulic acid-containing particles, and therefore has excellent ultraviolet absorbing properties.

[0083] <Cosmetic ingredients> The cosmetic raw material contains the above-mentioned ferulic acid-containing particles, and therefore has excellent ultraviolet absorbing properties.

[0084] <Action and effect> In the ferulic acid-containing particles, the content of ferulic acid is equal to or greater than a predetermined value, and the ferulic acid is uniformly dispersed in the inorganic particles, resulting in excellent ultraviolet absorbing properties.

[0085] Specifically, as a method for incorporating ferulic acid into cosmetics, a method is being considered in which ferulic acid-containing particles, in which ferulic acid is mixed with inorganic particles, are incorporated into the cosmetics.

[0086] However, there is a problem in that simply mixing ferulic acid with inorganic particles does not result in good ultraviolet absorbing properties.

[0087] On the other hand, in the ferulic acid-containing particles, a predetermined amount of ferulic acid is uniformly dispersed among inorganic particles, and therefore the particles have excellent ultraviolet absorbing properties. EXAMPLES

[0088] The present invention will be described in more detail below with reference to examples and comparative examples. The present invention is not limited to the examples and comparative examples. The specific numerical values ​​of the blending ratio (content ratio), physical property values, parameters, etc. used in the following description can be replaced with the upper limit (a numerical value defined as "equal to or less than") or lower limit (a numerical value defined as "equal to or more than" or "exceeding") of the corresponding blending ratio (content ratio), physical property values, parameters, etc. described in the above "Form for carrying out the invention".

[0089] <Ingredient details> Screw vial (20 mL): Maruem Mighty Vial (No. 5) Screw tube bottle (50 mL): Maruem Mighty Vial (No. 7) Hanil mixer: HANIL LAB.MIXER LM-110T, manufactured by Hanil Electronics Co., Ltd. Vacuum low-temperature dryer: VOS451-SD, cooling trap device UT-1000, diaphragm type vacuum pump EVP-1200, manufactured by Tokyo Rikakikai Co., Ltd. Ferulic acid: Ferulic acid, manufactured by Tsuno Rice Fine Chemicals Co., Ltd., serial number F09348 Ethanol: Ethanol (99.5), special grade reagent, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. Water: Distilled water, Fujifilm Wako Pure Chemical Industries, Ltd. Sodium lactate (50% aq): Aqueous solution of sodium lactate salt, solids concentration 50% by mass Sodium lactate (70% aq): Aqueous solution of sodium lactate salt, solids concentration 50% by mass Silica (GR1): Silica particles, product name "OVEIL GR1", average particle size 2.7 μm, manufactured by Mizusawa Industrial Chemicals Co., Ltd. Silica (GR2): Silica particles, product name "OVEIL GR2", average particle size 4.6 μm, manufactured by Mizusawa Industrial Chemicals Co., Ltd.

[0090] <Production of ferulic acid-containing particles> Examples 1 to 5 and Comparative Example 1 [1st step] Ferulic acid, ethanol, water, and a salt of a carboxyl group-containing compound were added to a screw cap bottle (20 mL) according to the formulation in Table 1, and the bottle was then closed and heated in a hot bath at 65°C for 10 minutes while shaking. This dissolved the ferulic acid, and a ferulic acid solution was obtained.

[0091] [Second process] According to the formulation in Table 1, inorganic particles were added to a Hanil mixer, and a part of the ferulic acid solution was added dropwise and stirred for 30 seconds. The dropwise addition and stirring process was repeated six times until all of the ferulic acid solution was added dropwise.

[0092] [3rd step] The mixture was dried overnight in a low-temperature vacuum dryer at 50° C. This allowed the alcohol and water to be dried off, yielding ferulic acid-containing particles.

[0093] Comparative Example 1 30.0 g of OVEIL GR1 and 7.5 g of ferulic acid powder were added to a Hanil mixer, stirred, and then dried overnight at 50° C. in a vacuum low-temperature dryer to obtain ferulic acid-containing particles.

[0094] <Evaluation> [Ratio of ferulic acid to ferulic acid-containing particles] For the ferulic acid-containing particles of each Example and Comparative Example, the content ratio of ferulic acid in the ferulic acid-containing particles was measured using a high performance liquid chromatograph (HPLC) under the following conditions. Specifically, the ferulic acid in the ferulic acid-containing particles was dissolved in dimethyl sulfoxide, diluted with acetonitrile, and used for measurement. The results are shown in Table 1. {conditions} Equipment: Shimadzu Corporation LC-20AD / CTO-20AC / SIL-20AC / CBM-20A / DGU-20A / SPD-M20A Column: Shodex HILICpak VG-50 2D manufactured by Resonac Inc.

[0095] [SEM Measurement] SEM measurements were performed on the ferulic acid-containing particles of each Example and Comparative Example. Specifically, a scanning electron microscope (SEM) "JSM-IT100" manufactured by JEOL Ltd. was used, and observations were performed at an acceleration voltage of 15 kV and a WD of 16 nm. Gold was evaporated onto the surface of the test specimen during the observation. The results are shown in Figures 1 to 6. In Example 1 (Figure 1) and Example 4 (Figure 4), crystals of ferulic acid deposited on the surface of inorganic particles were observed. The major and minor diameters of the crystals are shown in Figures 1 and 4. In Comparative Example 1 (Figure 6), crystals of ferulic acid independent of inorganic particles were observed. The major and minor diameters of the crystals are shown in Figure 6. In Example 2 (Figure 2), Example 3 (Figure 3), and Example 5 (Figure 5), crystals of ferulic acid deposited on the surface of inorganic particles and crystals of ferulic acid independent of inorganic particles were not observed.

[0096] [Uniformity] For the ferulic acid-containing particles of each Example and each Comparative Example, whether ferulic acid is uniformly dispersed in the inorganic particles was confirmed based on SEM, based on the crystals of ferulic acid independent of the inorganic particles (independent crystals) and the crystals of ferulic acid deposited on the surface of the inorganic particles (deposited crystals). The uniformity was evaluated based on the following criteria. The results are shown in Table 1. {standard} ◯: No independent crystals (at least crystals with a major axis exceeding 11.0 μm or a minor axis exceeding 5.0 μm) were observed. Also, no deposited crystals were observed. △: No independent crystals (at least crystals having a major axis exceeding 11.0 μm or a minor axis exceeding 5.0 μm) were observed. Furthermore, no deposited crystals were observed whose major axis exceeded 11.0 μm or whose minor axis exceeded 5.0 μm, but deposited crystals whose major axis was 11.0 μm or less and whose minor axis was 5.0 μm or less were observed. ×: Independent crystals (crystals with at least a major axis exceeding 11.0 μm or a minor axis exceeding 5.0 μm) were observed. Or, deposited crystals with at least a major axis exceeding 11.0 μm or a minor axis exceeding 5.0 μm were observed.

[0097] [UV absorption] The ultraviolet absorbing property was measured for the ferulic acid-containing particles of each Example and Comparative Example. Specifically, a 1 mm thick transparent PET partition plate was cut into 6.5 cm x 6.5 cm, and the center was cut out into a circle with a diameter of 5 cm. Then, 3M Transpore Tape Surgical Tape (1527-2) was applied so that the circle was hidden. Next, 3M White Surgical Tape (1534-2) was layered and applied, and 20 ± 1 mg of ferulic acid-containing particles (powder) was evenly placed on the adhesive surface, and the SPF value and UVA value were measured at 9 random points using Labsphere SPF Analyzer UV-2000S. The results are shown in Table 1.

[0098] [Touch] The ferulic acid-containing particles of each Example and Comparative Example were evaluated for their texture when applied to the back of the hand with a finger. Five subjects scored the samples according to the following evaluation criteria, and the average score was calculated. The texture was evaluated based on the following criteria. The results are shown in Table 1. In Table 1, the numbers in parentheses indicate the average value. {Evaluation criteria} No hard particles at all. 2 points Hard particles were occasionally present. 1 point Hard particles were clearly present. 0 points {standard} ○: The average score was 1.5 points or more. △: The average value was 0.5 points or more and less than 1.5 points. ×: The average value was less than 0.5 points.

[0099] [Sensory evaluation of face powder (loose type) formulation] 40 parts by mass of ferulic acid-containing particles of each Example and Comparative Example, 40 parts by mass of mica (surface-treated product, product name "LL-5 MICA Y-2300", manufactured by Daito Kasei Kogyo Co., Ltd.), 3.5 parts by mass of silica (OVEIL DR1, manufactured by Mizusawa Kagaku Kogyo Co., Ltd.), and 5 parts by mass of pigment-grade titanium dioxide (surface-treated product, product name "LL-5 TiO2 CR-50", manufactured by Daito Kasei Kogyo Co., Ltd.) were dry-mixed twice for 1 minute using a Hanil mixer (HANIL LAB.MIXER LM-110T, manufactured by Hanil Electric Co., Ltd.), and then 1.5 parts by mass of meadowfoam oil (CROPURE MEADOWFOAM, manufactured by Croda Japan Co., Ltd.) were added, and further mixing was performed three times for 1 minute. In this way, a face powder (loose type) containing ferulic acid-containing particles was produced.

[0100] The obtained face powder was evaluated for its texture when applied to the back of the hand with the fingers. Five subjects assigned scores according to the following evaluation criteria, and the average score was calculated. The texture was evaluated based on the following criteria. The results are shown in Table 1. In Table 1, the numbers in parentheses indicate the average value. {Evaluation criteria} No hard particles at all. 2 points Hard particles were occasionally present. 1 point Hard particles were clearly present. 0 points {standard} ○: The average score was 1.5 points or more. △: The average value was 0.5 points or more and less than 1.5 points. ×: The average value was less than 0.5 points.

[0101] <Consideration> According to the SEM measurement, it is found that ferulic acid is uniformly dispersed in the inorganic particles in Examples 1 to 5. Therefore, the ultraviolet ray absorbency can be improved.

[0102] On the other hand, in Comparative Example 1, ferulic acid crystals separate from the inorganic particles are precipitated, and it is found that ferulic acid is not uniformly dispersed among the inorganic particles, and therefore good ultraviolet absorbing properties cannot be achieved.

[0103] [Table 1]

Claims

1. A ferulic acid-containing particle comprising inorganic particles and ferulic acid, The content of the ferulic acid is 5% by mass or more relative to the ferulic acid-containing particles, A ferulic acid-containing particle, in which the ferulic acid is uniformly dispersed among the inorganic particles.

2. The ferulic acid-containing particles according to claim 1 , having an SPF value of 20 or more.

3. An ultraviolet absorber comprising the ferulic acid-containing particles according to claim 1 or 2.

4. A cosmetic raw material comprising the ferulic acid-containing particles according to claim 1 or 2.